2012
DOI: 10.1242/dmm.010009
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of weight loss under total starvation: evidence against the thrifty-gene hypothesis

Abstract: SUMMARYThe thrifty-gene hypothesis (TGH) posits that the modern genetic predisposition to obesity stems from a historical past where famine selected for genes that promote efficient fat deposition. It has been previously argued that such a scenario is unfeasible because under such strong selection any gene favouring fat deposition would rapidly move to fixation. Hence, we should all be predisposed to obesity: which we are not. The genetic architecture of obesity that has been revealed by genome-wide associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 117 publications
0
31
0
1
Order By: Relevance
“…I will therefore also draw on some examples in the literature of studies on such animals. Several other publications contain useful information on similar issues that are directly pertinent to the measurement of energy metabolism in the mouse and the reader may also wish to consult these, in particular the papers by Weir (1949), Kleiber (1961), Ferrannini (1988), Simonson and deFronzo (1990), Bursztein et al (1989), Elia and Livesey (1992), Even et al (1994), Arch et al (2006), Lighton (2008), Tschoep et al (2012), Even and Nadkarni (2012), Speakman et al (2013). …”
Section: Overviewmentioning
confidence: 99%
“…I will therefore also draw on some examples in the literature of studies on such animals. Several other publications contain useful information on similar issues that are directly pertinent to the measurement of energy metabolism in the mouse and the reader may also wish to consult these, in particular the papers by Weir (1949), Kleiber (1961), Ferrannini (1988), Simonson and deFronzo (1990), Bursztein et al (1989), Elia and Livesey (1992), Even et al (1994), Arch et al (2006), Lighton (2008), Tschoep et al (2012), Even and Nadkarni (2012), Speakman et al (2013). …”
Section: Overviewmentioning
confidence: 99%
“…A considerable body of scientific evidence has shown that obesity is a heritable condition [55, 56]. Several decades ago, this observation led to the development of the “thrifty gene” hypothesis (TGH) [57], which posits that human populations subjected to millennia of feast-or-famine conditions naturally select for genes that promote rapid weight gain in times of food surplus.…”
Section: Mechanisms and Potential Interventionsmentioning
confidence: 99%
“…First, human genes are only loosely tied to race/ethnic background; indeed, there is substantially more genetic variability within than between race/ethnic groups [60]. Second, while recent genome-wide association studies affirm that specific genes—including the fat mass and obesity associated gene ( FTO ) and melanocortin 4 receptor gene ( MC4R )—are associated with obesity [55], these associations are not consistently observed across race/ethnic groups and explain only a small proportion of population variability in body weight [55, 56, 61]. This makes the notion of a thrifty gene (or genes) seem unlikely as a singular explanation for large race/ethnic disparities in obesity.…”
Section: Mechanisms and Potential Interventionsmentioning
confidence: 99%
“…This idea has been called the thrifty gene hypothesis (11, 18, 41, 50, 56 -58, 77, 78). During complete starvation, individuals storing more fat can survive longer than individuals who store less (65,71), hence the thrifty gene hypothesis posits that, under conditions of uncertain food supply, genes promoting fat storage will be positively selected. The probability of a catastrophic failure of supply, however, diminishes as the duration of the period without food increases (FIGURE 3A).…”
Section: Long-term Regulation Of Energy Balance and Fat Storagementioning
confidence: 99%